If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(z + -2) + 2z = 7z + 3(x + -2) Reorder the terms: 6(-2 + z) + 2z = 7z + 3(x + -2) (-2 * 6 + z * 6) + 2z = 7z + 3(x + -2) (-12 + 6z) + 2z = 7z + 3(x + -2) Combine like terms: 6z + 2z = 8z -12 + 8z = 7z + 3(x + -2) Reorder the terms: -12 + 8z = 7z + 3(-2 + x) -12 + 8z = 7z + (-2 * 3 + x * 3) -12 + 8z = 7z + (-6 + 3x) Reorder the terms: -12 + 8z = -6 + 3x + 7z Solving -12 + 8z = -6 + 3x + 7z Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '-7z' to each side of the equation. -12 + 8z + -7z = -6 + 3x + 7z + -7z Combine like terms: 8z + -7z = 1z -12 + 1z = -6 + 3x + 7z + -7z Combine like terms: 7z + -7z = 0 -12 + 1z = -6 + 3x + 0 -12 + 1z = -6 + 3x Add '12' to each side of the equation. -12 + 12 + 1z = -6 + 12 + 3x Combine like terms: -12 + 12 = 0 0 + 1z = -6 + 12 + 3x 1z = -6 + 12 + 3x Combine like terms: -6 + 12 = 6 1z = 6 + 3x Divide each side by '1'. z = 6 + 3x Simplifying z = 6 + 3x
| 2u(3u+4)+3u(2u+1)= | | 6x-28=2x | | g-5=4 | | 2(3z-4)+1=3(z+1) | | -7x+1=-10 | | 7x=6x-12 | | 7x+1=-10 | | 3.2x+4(x+0.7)=38.8 | | 4y=3y+12 | | 5y=11x+15 | | 3x+9x+(12-2x)=2 | | 6-2(x+4)=108 | | 5x+9x-4-6x=12 | | m-3=23 | | 3x+6=y+4 | | 5(2x-1)-2(3x)=1 | | -s=90 | | 5x-(3+2x)=9 | | 6+3x=4+y | | 7y-11+y-3y=9 | | 4(3x+3)-7x=22-5x | | r+7=21 | | 3x+(2+4x)=23 | | -8(45y+18)=3(12y+18) | | -1.2x=4.08 | | 4x-4y+6x-8x+6y= | | 0.7t=-0.98 | | -12.75+5.95= | | 6.1g=3.66 | | 7x+3+5x+9=11x+4 | | 55=11k | | 9(x+2)-3(x-2)=0 |